Instruments to identify risk factors associated with adverse childhood experiences for vulnerable children in primary care in low- and middle-income countries: A systematic review and narrative synthesis. - Winfrida Mwashala; Udoy Saikia; Diane Chamberlain (Public Library of Science (PLoS), 2022)
Vulnerable children exposed to Adverse Childhood Experiences (ACEs) are lacking visibility in healthcare and social welfare support systems, particularly in countries where there are delays in integrating biopsychosocial care into traditional medical care. This review seeks to identify, evaluate, and summarise existing screening instruments used in measuring risks factors related to Adverse Childhood Experiences (ACEs) in vulnerable children in Primary Health Care (PHC) settings in low- and middle-income countries (LMICs). The target population in this research is children from age (05-18 years) living in poverty and extreme social disadvantage. First, a systematic review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. A mixed-methods narrative synthesis analyzed the studies and instruments used to assess vulnerable children exposed to ACEs. Each instrument was scrutinized for quality, validity, and feasibility for use with vulnerable children in frontline clinical settings. There is a lack of suitable risk assessment instruments to identify biopsychosocial risk factors from exposure to ACEs in vulnerable children in LMIC primary healthcare settings. Among nine identified instruments from the reviewed studies, none were found suitable for rapidly identifying the effects of ACEs. This was due to issues on the reviewed instruments which could hinder their application in the rapid screening of ACEs in frontline clinical settings. This included the, retrospective nature of the instruments, decisional capacity of the rater, institutional capacity in implementation of the instruments and instruments capacity to assess individual risk factors in biopsychosocial dimensions. Therefore, currently, there is lack of instruments that can be used to identify biopsychosocial risk factors of ACEs in vulnerable children in primary care in limited-resource settings. Further development of an instrument for the rapid identification of ACEs in vulnerable children is required for an early recognition and referred for preventive care, treatment, and social support services.